Seroprevalence and distribution of leptospiral serovars in livestock (cattle, goats and sheep) in flood-prone Kelantan, Malaysia - Abdul Rahman, Mohammad Sabri; Bejo, Siti Khairani; Zakaria, Zunita; Hassan, Latiffah; Roslan, Mohd Azri (Sciendo, 2021)
Introduction: Leptospirosis is a bacterial disease that affects both humans and animals, the occurrence of which increases markedly during and after heavy rainfall and flooding. The aim of this study was to determine the serological prevalence of leptospiral infection in livestock after a voluminous flood in 10 districts of the Malaysian state of Kelantan. Material and Methods: In December 2014, Kelantan was hit by an extensive flood. A total of 1,728 serum samples were collected from livestock from the state, comprised of 1,024 from cattle, 366 from goats and 338 from sheep, and they were tested using the microscopic agglutination test (MAT). Results: Altogether, 203 (11.75%; 203/1728; 95% CI: 10.20%–13.30%) of the tested sera were found to be positive serologically. Cattle had the highest prevalence of 14.16% (145/1024), while goats and sheep had 11.20% (41/366) and 5.03% (17/338) respectively. The most frequent serovars detected were Hardjo-bovis (3.70%; 64/1728), Hebdomadis (2.08%; 36/1728) and Pomona (1.04%; 18/1728). There was a statistically significant association (P < 0.05) between livestock that were exposed to the flood and seropositivity. Conclusion: This study showed that flood is a risk factor that can play a role in the epidemiology of leptospiral infection in livestock.